Cetyltrimethylammonium bromide intercalated and branched polyhydroxystyrene functionalized montmorillonite clay to sequester cationic dyes. (1st August 2018) - Kenawy, El-Refaie; Ghfar, Ayman A.; Wabaidur, Saikh Mohammad; Khan, Moonis Ali; Siddiqui, Masoom Raza; Alothman, Zeid A.; Alqadami, Ayoub Abdullah; Hamid, Muhammad
Abstract: Herein, Cetyltrimethyl ammonium bromide (CTAB) intercalated and branched polyhydroxystyrene (BPS) functionalized montmorillonite (MMT) nano-composite (BPS-CTAB-MMT) was developed, characterized, and its potential as an adsorbent was tested in sequestering cationic dyes viz. rhodamine B (RB), crystal violet (CV), and methylene blue (MB) from aqueous environment. N2 adsorption/desorption isotherm showed mesoporous BPS-CTAB-MMT surface with a BET surface area of 273.8 m 2 /g. The appearance of sharp spikes at 2855 and 2925 cm −1 (associated with symmetric and asymmetric tensions of C – H bonds) in infra-red spectrum of BPS-CTAB-MMT indicates successful intercalation of MMT with CTAB and functionalization with BPS. The observed crystallite size of BPS-CTAB-MMT was 66 nm. Comparatively greater weight loss for BPS-CTAB-MMT (11%) than MMT (9%) was observed during thermogravimetric analysis. The adsorption of dyes on BPS-CTAB-MMT was pH dependent with maximum uptake was observed in the pH range: 5–6. For initial dyes concentration (Co ) range: 50–150 mg/L, the observed equilibration time for CV was 300 min, whereas for RB and MB the equilibration time varied between 300 and 360 min. Modeling investigations revealed the applicability of Sips isotherm and pseudo-second-order (PSO) kinetic models to dyes adsorption data. Sips maximum adsorption capacity (qs ) values for RB, CV, and MB at 55 °C were 476.5, 438.7, and 432.7 mg/g, respectively. The adsorption of dyes on BPS-CTAB-MMT was thermodynamically favorable. Desorption studies showed 42.1% RB and 41.9% CV recovery with 0.1 M NaOH and CH3 COCH3, respectively, while only traces of MB were recovered with tested eluents. Graphical abstract: Highlights: BPS-CTAB-MMT nanocomposite was developed to sequester cationic dyes. BPS-CTAB-MMT was thermally stable and mesoporous with 273.8 m 2 /g BET surface area. Sips isotherm and PSO kinetic models were fitted to RB, CV, and MB adsorption data. The q s values at 55 °C for RB, CV, and MB were 476.5, 438.7, and 432.7 mg/g. 42.1% RB and 41.9% CV were recovered with 0.1 M NaOH and CH3 COCH3, respectively.